Cerita Bergambar Motivasi Shalat Untuk Anak-anak - Rahmad Fikran; San Ahdi (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2023)
Habituation is a very effective way to educate children in matters of worship. During the process of teaching children to pray five times a day, the attitude of children who are so busy with their play world is a common obstacle felt by parents. Because of that, the designer is interested in presenting Islamic literacy that conveys the motivation of prayer for children. Designers obtain data through surveys, observations and literature studies, then designers analyze the data as problem solving with the 5W + 1H method (what, who, when, why, where, and how). Meanwhile, the design method used is the 4D Model (Define, Design, Development, and Disseminate). The resulting Islamic literacy media design is a picture storybook entitled "Jangan Lalaikan Shalat".